Genomic insights into blaAFM-positive carbapenem-resistant Pseudomonas aeruginosa in China - Lu, Huimin; Zhang, Chuanjun; Zhao, Buhui; Li, Yan; Qin, Shangshang (Frontiers in Microbiology, 2025)
Carbapenem-resistant Pseudomonas aeruginosa (CRPA) poses a global threat; however, the epidemiological characteristics and clinical significance of blaAFM-positive CRPA strains in China remain unclear. In this study, continuous surveillance was conducted from 2018 to 2022 in a hospital in Henan Province, China, and the genomic characteristics of blaAFM-positive CRPA were elucidated. We characterised the genetic features of blaAFM-positive CRPA isolates by antimicrobial susceptibility testing, conjugation assays, whole-genome sequencing, large-scale comparative genomics, and bioinformatic analyses. Among 628 CRPA isolates, one blaAFM-positive multidrug-resistant (MDR) strain, PA19-3158 (ST1123), was identified, with the blaAFM-1 gene located on a novel 518,222 bp megaplasmid. Additionally, big data analysis revealed the genomic characteristics of blaAFM-positive CRPA across China. A total of three different blaAFM gene variants were identified among these isolates, namely blaAFM-1 (44.12%), blaAFM-2 (52.94%), and blaAFM-4 (2.94%). Our findings identified ST463 as the dominant clone among blaAFM-positive CRPA in different regions of China, with some blaAFM-positive CRPA isolates from these regions exhibiting high genetic similarity. Notably, all blaAFM-positive CRPA isolates carried multiple antibiotic resistance genes (ARGs), with approximately 38% co-harboring the carbapenem-resistant gene blaKPC-2 and approximately 47% co-harboring the tigecycline-resistant gene tmexCD-toprJ. Correlation analysis underscored the significant role of mobile genetic elements in facilitating blaAFM gene transfer. These results highlight the critical need for continuous surveillance of blaAFM-positive CRPA in clinical settings to mitigate potential risks.